2016
DOI: 10.3762/bjnano.7.59
|View full text |Cite
|
Sign up to set email alerts
|

Comparative kinematical analyses of Venus flytrap (Dionaea muscipula) snap traps

Abstract: SummaryAlthough the Venus flytrap (Dionaea muscipula) can be considered as one of the most extensively investigated carnivorous plants, knowledge is still scarce about diversity of the snap-trap motion, the functionality of snap traps under varying environmental conditions, and their opening motion. By conducting simple snap-trap closure experiments in air and under water, we present striking evidence that adult Dionaea snaps similarly fast in aerial and submersed states and, hence, is potentially able to gain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 33 publications
(39 reference statements)
3
27
0
Order By: Relevance
“…In this context, a detailed investigation of fluid displacement during closure between the two species is of high interest and worth further research. This has been stated in [4], where we show that Dionaea traps also function under water, and therefore, prove that the viscosity of the surrounding medium (air versus water) seems not to be the main constraint for the evolution of the different types of snap-trap actuation found in Aldrovanda and Dionaea.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In this context, a detailed investigation of fluid displacement during closure between the two species is of high interest and worth further research. This has been stated in [4], where we show that Dionaea traps also function under water, and therefore, prove that the viscosity of the surrounding medium (air versus water) seems not to be the main constraint for the evolution of the different types of snap-trap actuation found in Aldrovanda and Dionaea.…”
Section: Discussionsupporting
confidence: 86%
“…Consequently, kinematic amplification would be a suitable way to achieve sufficiently fast and 'economic' plant motions for small structures. This is further confirmed by the fact that traps of juvenile Dionaea, which are similar in size to those of adult Aldrovanda, do not yet employ snap-buckling for closure but presumably move purely hydraulically, yet much slower than Aldrovanda traps [4]. As shown in this study, the faster snapping motion in Aldrovanda can, in turn, be explained by the speed boost due to the incorporated prestress.…”
Section: Discussionsupporting
confidence: 78%
“…The authors showed that minute seedling traps are much slower and do not yet incorporate elastic instabilities responsible for the fast motion. These findings are discussed in biomechanical and biomimetic contexts [ 10 ].…”
Section: Plant Systemsmentioning
confidence: 99%
“…In addition to the fields of botanical–biomimetic research, Wilhelm Barthlott has significantly contributed to many other fields of botany, for example, systematics and functional morphology of carnivorous plants and epiphytic cacti, biogeography/biodiversity and pollination biology (UV signatures). Some of these topics have become objects of interest in biomimetic research and are partially covered in articles in this Thematic Series [ 10 11 ].…”
mentioning
confidence: 99%
“…The energy consumption of D. muscipula for one trap closure is ~300 μmol ATP, equivalent to 9.66 J (Jaffe, 1973 ) (ATP hydrolysis consumes roughly 30.5 kJ/mol (Rosing and Slater, 1972 ). Reopening, after prey capture and digestion, occurs over 1–2 days Fagerberg and Howe, 1996 ; Volkov et al, 2014 ; Poppinga et al, 2016 , 2018 ). It is controlled either by irreversible growth processes (Ashida, 1934 ) or by hydrostatic pressure changes within the lobes (Markin et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%